1988
DOI: 10.1111/j.1432-1033.1988.tb14349.x-i2
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity‐dependent energy barriers and equilibrium conformational fluctuations in oxygen recombination with hemerythrin

Abstract: The recombination kinetics of photo-dissociated oxyhemerythrin (Sipunculus nudus) have been investigated between 298 K and 90 K. Fast geminate recombinations compete with oxygen escape into the solvent, from which a subsequent slower bimolecular rebinding takes place. In phosphate buffer @H 7.7) at 278 K, the fast and slow processes are exponential and have comparable amplitudes. Whereas the oxygen escape rate rapidly decreases upon increasing the viscosity, the inward rate from the solvent is found to be inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 39 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…It is worthwhile to point out that a similar trend of the rate constants k CA and k CS as a function of viscosity was observed previously for oxygen binding to hemerythrin following nanosecond laser flash photolysis. 77 In that case, the authors discussed the observed different viscosity dependence of the rate constants for the rebinding from the protein matrix and from the solution as arising from the different pathways followed by the ligand in the two processes. The authors concluded that hemerythrin undergoes a conformational transition upon ligand binding, which closes an exit channel necessary for ligand escape.…”
Section: Resultsmentioning
confidence: 99%
“…It is worthwhile to point out that a similar trend of the rate constants k CA and k CS as a function of viscosity was observed previously for oxygen binding to hemerythrin following nanosecond laser flash photolysis. 77 In that case, the authors discussed the observed different viscosity dependence of the rate constants for the rebinding from the protein matrix and from the solution as arising from the different pathways followed by the ligand in the two processes. The authors concluded that hemerythrin undergoes a conformational transition upon ligand binding, which closes an exit channel necessary for ligand escape.…”
Section: Resultsmentioning
confidence: 99%
“…Although the gas pressure decreased approximately threefold upon cooling, reequilibration of the dissolved gases due to pressure change or to change of solubility with temperature is not expected to occur over the duration of the experiments, owing to the very high viscosity of the cold glycerol/water solvent. The solubility of xenon at room temperature was taken as 4.4 mM/atm in water (Rubin et al, 2002), and 1.1 mM/atm in 79% glycerol, assuming a reduction factor of the solubility due to the presence of 79% glycerol similar to that measured for O 2 (Lavalette and Tetreau, 1988).…”
Section: Sample Preparation and Data Collectionmentioning
confidence: 99%
“…It is known that CO is able to detectably escape or enter the protein down to 200 K in 79% glycerol/ water (w/w). Because these processes are essentially regulated by the viscosity damping of fluctuations at the protein surface (Beece et al, 1980;Lavalette and Tetreau, 1988) we may assume that this temperature limit remains approximately the same for xenon and CO. Extrapolation of the Arrhenius plot of the equilibrium constant (Fig.…”
Section: Taxonomic Conformational Substates In the Presence Of Xenon (T < T G )mentioning
confidence: 99%
See 1 more Smart Citation
“…Some other earlier investigations also found reduced overdamping of the isomerization rate of trans -stilbene versus alkane shear viscosity. , With regard to protein and enzyme reactions, numerous studies sought to examine the extent to which the Kramers basic result, set as a rate–friction inverse relationship ( k ∝ 1/η, where the hydrodynamic proportionality of solvent viscosity η and friction coefficient γ is used), can be observed. These studies have generally concluded that the rate–viscosity relationship holds as k ∝ η –n , where the exponent n lies in the 0–1 bound for a variety of reactions, including enzyme kinetics, protein folding, end-to-end intrachain looping in small peptides, inter- and intramolecular electron transfer processes, , the photodissociation rate in oxygen complexes of myoglobin and hemerythrin, , ligand binding to myoglobin, and amide hydrogen exchange in some proteins. A recent single-molecule study also finds a fractional viscosity exponent . Taking all literature data at face values under experimental conditions used, one might suppose that macromolecular reactions are as overdamped as the Kramers equation would, and underdamping in some cases could be due to a host of factors, including characteristic equilibrium thermal fluctuations, low-amplitude motions required for certain protein functions, , colored Gaussian noise, insufficient coupling of the reaction site with the bulk solvent, , and anomalous internal friction.…”
mentioning
confidence: 99%